Unique archaeal assemblages in the Arctic Ocean unveiled by massively parallel tag sequencing - Galand, Pierre E.; Casamayor, Emilio O.; Kirchman, David L.; Potvin, Marianne; Lovejoy, Connie (The ISME Journal, 2009)
10 páginas, 4 figuras, 1 tabla. The Arctic Ocean plays a critical role in controlling nutrient budgets between the Pacific and Atlantic Ocean. Archaea are key players in the nitrogen cycle and in cycling nutrients, but their community composition has been little studied in the Arctic Ocean. Here, we characterize archaeal assemblages from surface and deep Arctic water masses using massively parallel tag sequencing of the V6 region of the 16S rRNA gene. This approach gave a very high coverage of the natural communities, allowing a precise description of archaeal assemblages. This first taxonomic description of archaeal communities by tag sequencing reported so far shows that it is possible to assign an identity below phylum level to most (95%) of the archaeal V6 tags, and shows that tag sequencing is a powerful tool for resolving the diversity and distribution of specific microbes in the environment. Marine group I Crenarchaeota was overall the most abundant group in the Arctic Ocean and comprised between 27% and 63% of all tags. Group III Euryarchaeota were more abundant in deep-water masses and represented the largest archaeal group in the deep Atlantic layer of the central Arctic Ocean. Coastal surface waters, in turn, harbored more group II Euryarchaeota. Moreover, group II sequences that dominated surface waters were different from the group II sequences detected in deep waters, suggesting functional differences in closely related groups. Our results unveiled for the first time an archaeal community dominated by group III Euryarchaeota and show biogeographical traits for marine Arctic Archaea. P E Galand is supported by a Marie Curie grant (CRENARC MEIF-CT-2007–040247). EO Casamayor was supported by a Spanish grant CGL2006–12058-BOS, and D L Kirchman by NSF OPP ARC-0632233. C Lovejoy would like to acknowledge the support of the Natural Sciences and Engineering Council, Canada (NSERC) Special Research Opportunity Fund. We thank C Pedros-Alio for support during CASES. Deep Arctic samples were collected by K ...